Public Policy Analysis by The Government of Pati on Negative Impact of Prevention of Karaoke for The Tourism Businesses - Sema Ardianto; Widayati Widayati (Jurnal Daulat Hukum, 2018)
Pati Regency is a potential area in terms of tourism development, in addition to a relatively wide area is also crossed by lanes north coast. So often tourists from other regions that could pass stopover to rest and enjoy the tourism facilities in Pati. one tourism in Pati are tourism enterprises of karaoke. Karaoke tourism businesses experience rapid growth in every year. However, the tourism business is growing very rapidly karaoke if not offset by a provision concerning how the karaoke business is operational in accordance with properly, causing this karaoke tourism business potential for misuse to be a place of prostitution. Circumstances such as this would require local governments to adopt policies in addressing the phenomenon of tourism in the district of Pati. Especially tourism type of karaoke, karaoke business for the existence not adversely affect the community in the district of Pati. This research used socio-juridical approach. Data were obtained by means of field research, then the data is analyzed by qualitative descriptive analysis. The results showed that the measures taken by the District Government Pati experiencing constraints in its implementation in society.Keywords : Analysis, Public Policy, Tourism, Karaoke.